Experimental Investigation of Swirl Flow in a Ribbed Cylindrical Container using Particle Image Velocimetry - Tahir Javed (00000277727); Dr Majid Ali (USPCAS-E, NUST, Islamabad, 2022)
TH-423
Keywords: MS-TEE Thesis MSThesis